Corporate Social Responsibility Practices in Islamic Financial Institutions (IFIs) in Sri Lanka - Rifas, Abi Huraira; Mohamed Nafeel, Mohamed Mahboob; Misrina, Adampulle (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
The Islamic banking system is a rapidly growing segment in the global banking industry. Corporate Social Responsibility (CSR) is a crucial element in the field of Islamic banking as it consists of responsibilities and accountabilities to the com- munity. This study examined how CSR is practiced in Islamic Financial Institutions (IFIs) and its importance in Sri Lanka. The objective of the study is to examine the practices and im- portance of CSR practices in Amana Bank PLC and Al- Falaah (LOLC) PLC. The Primary data for the study were collected through interviews from selected branch managers and In- house Shari’ah advisers of the above IFIs. The findings of this study highlight the significance and the necessity of several CSR activities which are carried out by IFIs for the surround- ing community, such as charity services, sponsorship, medi- cal camps, educational assistance and social services. Inter- estingly, Amana Bank PLC has spent a higher amount for CSR activities relatively than Al-Falaah. In addition, it is directed for future research to study the comparison of CSR activities between IFIs and conventional financial institutions, and the impact of CSR on the society.